The Influence of Competency, Commitment Escalation, Individual Behavior on Personnel Performance Through Personnel Performance Motivation - Fazrial Kenedy; Indriyani Indriyani; Bambang Satriawan (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This research aims to determine the effect of competence on work motivation, the effect of escalation of commitment on work motivation, the effect of individual behavior on work motivation, the effect of competence on performance with work motivation as an intervening variable, the effect of escalation of commitment on performance with work motivation as an intervening variable, the effect of behavior individual performance with work motivation as an intervening variable. Research Background: The traffic directorate of the Riau Islands Regional Police has a vision of the Traffic Police being able to be protectors, guardians of public servants who are always close and together with the community as well as professional and proportional law enforcement officers who always uphold the supremacy of law and human rights, maintain security and orderliness and smoothness of traffic in the Riau Islands Province region Methods: Quantitative research methods are numerical and financial ratios. Results: The results of this research show that competence has a positive influence on performance, the influence of escalation of commitment on work motivation has a positive influence, the influence of individual behavior on work motivation has a positive influence, the influence of competence on performance with work motivation as an intervening variable has a positive influence, the influence of escalation of commitment on performance with motivation work as an intervening variable has a positive effect, and the influence of individual behavior on performance with work motivation as an intervening variable has a positive effect. Conclusion: The competency variable on personnel performance has a positive but not significant effect. The competency variable on work motivation has a positive but not significant effect. The competency variable on personnel performance through work motivation as an intervening variable has a positive but not significant effect.